Fit to Last? Investigating How Person-Job Fit and Person-Organization Fit Affect Turnover Intention in the Retail Context - Berisha, Gentrit; Lajçi, Rrezon (Organizations and Markets in Emerging Economies, 2020)
Retail supermarket chains face high turnover that creates costs and compromises customer satisfaction. Turnover intention is influenced by the fit or misfit of employees to the job and the organization, as well as their satisfaction with the job and the commitment to the organization. This paper investigates the relationship of person-job (P-J) and person-organization (P-O) fit with job satisfaction and organizational commitment. A total of 211 questionnaires from employees in the retail supermarket chains in Kosovo were collected. Regression analysis is used to test the relationships between fit constructs and work attitudes as outcomes and their effect on turnover intention. Bootstrap mediation is used to test the direct and indirect effect of fits on turnover intention. Results show that person-job fit and person-organization fit have a significant positive effect on job satisfaction and organizational commitment. All these constructs have a negative effect on turnover intention. P-J and P-O fit have a direct negative effect on turnover intention, which is also partially mediated by job satisfaction and organizational commitment. This paper supports previous evidence that P-J and P-O fit have a positive effect on work attitudes and eventually reduce turnover intention. The direct effect of fits on turnover intention is stronger than the indirect effect, mediated by job satisfaction and organizational commitment.